Situation Report: Romania, 30 December 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to Polish Events State Budget for 1971 Ministry of Tourism Established Economic Relations with Communist Countries Closer Co-operation with US Sought Financial Computer Center Set Up Reorganization of the Ministry of the Chemical Industry Restructuring of Industrial Centers